PENINGKATAN HASIL BELAJAR SISWA DENGAN MODEL KOOPERATIF TIPE SNOWBALL THROWING PADA PEMBELAJARAN SENI TARI KELAS VIIIC di SMP N 1 BUKITTINGGI - Vera Daniati; Yuliasma Yuliasma; Zora Iriani (FBS Universitas Negeri Padang, 2013)
Abstract This research is a classroom ction research conducted at SMPN 1 Bukittinggi, grade VIII C class because this class have the value of the lowest student from another class, namely the value ofthe average gradeis 71. The teacher used cooperative learning model snowball throwing type, where the learning model was a kind of ball throwing game filled with question related to the materials discussed in the class, which is useful for stimulating creativity, teamwork, participation and sense of responsibility of students to a given task. From the results of the study proved that the learning out comes of students has increased VIII C class better that in the first cycle students 'average score was 73 and the second cycle students' average score was 83. Kata kunci: Model Kooperatif Tipe Snowball Throwing, hasil belajar